Screening of Spirulina strains for high copper adsorption capacity through Fourier transform infrared spectroscopy - Liu, Jinghua; Zhu, Changwei; Li, Zhengpeng; Zhou, Haoyuan (Frontiers in Microbiology, 2022)
Microalgae have emerged as promising biosorbents for the removal of toxic metals from industrial effluents due to the presence of various free functional groups. While the constitutes are distinct among different algal strains, it needs to screen the algae with high adsorption capacities for heavy metal ions by analyzing the algal components. In this study, a rapid and nondestructive FT-IR method combined PCA algorithm was used to discriminate algal strains according to their cellular components. With FTIR spectroscopy, we have found that the algal strains for high copper adsorption capacity (RH44, XS58, AH53 and RZ22) can be well differentiated from other strains via assessing the components involved in the biosorption of copper ions at the spectral window range of 1200-900cm-1mainly attributed to polysaccharides. Correspondingly, the copper removal efficiency by different Spirulina strains was also measured by biochemical assay and scanning electron microscopy (SEM) in order to confirm the screening result. Compared with the chemical measurement, the assessment based on spectral features appears fairly good in evaluation and differentiation of copper adsorption capacity in various Spirulina strains. This work illustrates that FT-IR spectroscopy may serves as a fast and effective tool to investigate the functional groups for copper ions binding in the Spirulina cell and it even offers a useful and accurate new approach to rapidly assess potential adsorbents for high capacity of copper adsorption.